A novel method for imaging the pharmacological effects of antibiotic treatment on Clostridium difficile. (August 2016) - Endres, Bradley T.; Bassères, Eugénie; Memariani, Ali; Chang, Long; Alam, M. Jahangir; Vickers, Richard J.; Kakadiaris, Ioannis A.; Garey, Kevin W.
Abstract: Clostridium difficile is a significant cause of nosocomial-acquired infection that results in severe diarrhea and can lead to mortality. Treatment options for C . difficile infection (CDI) are limited, however, new antibiotics are being developed. Current methods for determining efficacy of experimental antibiotics on C . difficile involve antibiotic killing rates and do not give insight into the drug's pharmacologic effects. Considering this, we hypothesized that by using scanning electron microscopy (SEM) in tandem to drug killing curves, we would be able to determine efficacy and visualize the phenotypic response to drug treatment. To test this hypothesis, supraMIC kill curves were conducted using vancomycin, metronidazole, fidaxomicin, and ridinilazole. Following collection, cells were either plated or imaged using a scanning electron microscope (SEM). Consistent with previous reports, we found that the tested antibiotics had significant bactericidal activity at supraMIC concentrations. By SEM imaging and using a semi-automatic pipeline for image analysis, we were able to determine that vancomycin and to a lesser extent fidaxomicin and ridinilazole significantly affected the cell wall, whereas metronidazole, fidaxomicin, and ridinilazole had significant effects on cell length suggesting a metabolic effect. While the phenotypic response to drug treatment has not been documented previously in this manner, the results observed are consistent with the drug's mechanism of action. These techniques demonstrate the versatility and reliability of imaging and measurements that could be applied to other experimental compounds. We believe the strategies laid out here are vital for characterizing new antibiotics in development for treating CDI. Highlights: Comparison of four Clostridium difficile active antibiotics: vancomycin, metronidazole, fidaxomicin, and ridinilazole. Semi-automatic analysis pipeline of bacterial SEM images demonstrates different antibiotics have altering effects on the cell wall and cell length. This study highlights the utility of this strategy for determining the killing action of different antibiotics.